DAMPAK PENDIDIKAN DAKWAH DAN LANDASANNYA DALAM MASYARAKAT ISLAM - Mohammed Ramadan Abraheem Alshaykh Ali; Hakiki Rikza Irnaini Al Badri (Universitas Islam Malang, 2022)
The Book of Allah is the source of legislation and the source of Islamic islamic islamic provisions, and the Qur'an has approached several methods and means to correct behavior and guide man to the right path, with the statement of halal and haram, and the Qur'an has taken the style of stories to show what is meant and guide people to the right, and scholars of interpretation and jurists in this area in particular, because it is the basis of the evaluation of the nation and the establishment of an Islamic generation on the approach of the Book and the Prophet's Sunnah. The objectives of this research mean (1) to know the formation of the features of education and advocacy identified by the scholars of interpretation, (2) to know the formation of the methods of education and advocacy derived from the books of interpretation, (3) to find out the impact of advocacy education and its foundations in the Islamic society. The researcher used the type of descriptive office search. The way data is collected in this research is documentation. The data used in this research are preliminary data that prophetic and secondary data after obtaining the data. The researcher analyzed the data using miles and Huberman model analysis techniques. The results of this research mean (1) that the parameters of education and educators must follow the example of prophets and apostles, (2) the methods of education and advocacy derived from the Holy Quran and the Prophet's Sunnah, (3) that advocacy education has great benefits, benefits the individual and society, and raises generations a valid education on the platform of prophecy.